PENGARUH PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK DENGAN MEDIA WORDWALL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SD DITINJAU DARI GAYA BELAJAR - Dewi Putri Yuni; Jamaris Jamna; Yumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the Realistic Mathematics Education (RME) approach assisted by Wordwall media on the mathematical problem-solving abilities of fifth-grade elementary school students, viewed from the perspective of learning styles. The research employed a quasi-experimental method with a Pretest-Posttest Control Group Design involving two classes: an experimental class that received RME-based instruction using Wordwall, and a control class that received conventional instruction. Data were collected through tests, classroom observation, and learning style questionnaires, and analyzed using t-tests, two-way ANOVA, and post hoc follow-up tests. The results indicated a significant difference between the experimental and control groups, with the RME approach using Wordwall being more effective in enhancing students' problem-solving skills. Moreover, learning styles were found to significantly influence learning outcomes; however, no significant interaction was identified between the learning approach and learning style. The post hoc test results revealed that students with visual and auditory learning styles scored higher than those with kinesthetic styles. The RME approach supported by Wordwall media is recommended as an inclusive and adaptive instructional strategy that accommodates diverse student learning styles.